Framing Berita Pengelolaan Sampah di Indonesia pada Media Daring Detik.com dan Antaranews.com - Faisal Reza Baihaqi; Hendra Setiawan; Uah Maspuroh (Jurnal Sinestesia, 2022)
This study aims to explain how Detik.com and Antaranews.com frame news about waste management in Indonesia in the period January-May 2022. During that time, news articles were narrowed down based on search keyword for waste management so tahat 24 news items were obtained from Detik.com and Antaranews.com as the purposive sample. Thus, a qualitative approach with a constructionist paradigm is used. The framing analysis used in this study is the Zhongdang Pan and Gerald M. Kosicki model which dissects four structures to see the news frame, namely syntactic, script, thematic, and rhetorical structures. The framing theory is to see the tendency of Detik.com and Antaranews.com reporting in reporting problems. The result show that Detik.com and Antaranews.com tend to report on waste management problems with the type of hardnews news, news is also viewed by consensus by Detik.com and Antaranews.com as common problem but the government is the main actor in implementing policies. Detik.com and Antaranews.com do not include the principle of cover both sides in reporting on waste management in Indonesia, Detik.com and Antaranews.com tend to highlight government policies and do not cause problems from the community side.